Development of improved technology for producing graphene-like coating by LPCVD method - Iatsenko, Artem (Technology audit and production reserves, 2023)
The object of research in this work was the coating of oxygraphene on a silicon single crystal substrate. In the work, the LPСVD (Low Pressure Chemical Vapor Deposition) method of deposition from the gas phase at low pressure is used to obtain graphene-like coatings on heat-resistant materials. A feature of the proposed LPCVD method in comparison with the classical method of deposition from the gas phase CVD (Chemical Vapor Deposition) by the method of catalytic decomposition of carbon-containing gas followed by the deposition of a graphene-like coating on a copper template is the use of a higher partial gas pressure, which leads to the deposition of graphene-like waste not only on the surface of the copper template-catalyst, but also in the entire volume of the reaction chamber and the materials introduced into it. A monocrystalline silicon template was used as a model for coating. The resulting coatings of different thicknesses were examined by scanning electron microscopy, Raman spectroscopy, and density was assessed by helium pycnometry. Based on the analysis of the results obtained using the method of scanning electron microscopy, the possibility of varying the thickness of the oxygraphene coating was shown. In addition, the formation of oxygraphene on a silicon single crystal substrate was confirmed by the Raman spectroscopy method, namely the presence of characteristic peaks in the spectra of the studied materials. Using the helium pycnometry method, a decrease in the density of the coated material from 2.25 g/cm3 to 2.08 g/cm3 was found. It was established that the greater the coating thickness, the lower the density. The general analysis showed that the developed LPСVD technology allows obtaining an oxygraphene coating on materials of any shape, porosity, size and resistant to temperatures above 600 °С in order to functionalize their surface and improve and improve their properties.